The Benefits of Flavonoids in Diabetic Retinopathy - Matos, Ana L (2020)
Diabetic retinopathy (DR), one of the most common complications of diabetes, is the leading cause of legal blindness among adults of working age in developed countries. After 20 years of diabetes, almost all patients suffering from type I diabetes mellitus and about 60% of type II diabetics have DR. Several studies have tried to identify drugs and therapies to treat DR though little attention has been given to flavonoids, one type of polyphenols, which can be found in high levels mainly in fruits and vegetables, but also in other foods such as grains, cocoa, green tea or even in red wine. Flavonoids have anti-inflammatory, antioxidant and antiviral effects. Since it is known that diabetes induces oxidative stress and inflammation in the retina leading to neuronal death in the early stages of the disease, the use of these compounds can prove to be beneficial in the prevention or treatment of DR. In this review, we summarize the molecular and cellular effects of flavonoids in the diabetic retina.